PELABELAN L(d,2,1) PADA OPERASI KOMPLEMEN DAN KORONA GRAF LINTASAN DAN SIKLUS - Natalia, R; Sudarsana, I W; Musdalifah, S (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
Let  be a graph with  vertices and  edges. An  labeling of graph  is a function of    such that the following condition  for  where denoted the on distance of two vertices  and   and  for . A number  is called the span of  labeling, if  is the largest label vertex of  labeling. Notation   states that the smallest span of all labeling on a graph . An injective labeling is called  and a minimum span of all labeling  denoted by . A graph  which has  labeling is called the  graph. In this paper we study of such labeling by considering complement of path and cycle. The result showed that complement of path  has , for  and , for  and complement of the cycle  has for  and , for  and  corona of two paths  has . Therefor, the complement of paths  the complement of cycle , and  corona of two path  are  graph.